A Literature Review on Awareness and Factors of Consumers Behaviour Towards ‎Crowdfunding - SHUAIB, SUKAYNAH; QAZI, HARIS SAQIB (International Journal of Islamic Economics and Governance, 2022)
Crowdfunding, which has made it possible for individuals to directly support others who need financial assistance in an emergency, has changed the landscape of traditional fundraising in recent years. This has helped to break down barriers and fuel the rising trend of individual giving. The aim of this research is to identify the awareness and factors that affect consumer behavior towards crowdfunding. This study explores the awareness and different possible factors that affect consumer behavior towards crowdfunding. The methodology used in this research is based on previous studies conducted on consumer behaviors, awareness, and attitudes towards crowdfunding. Findings show more awareness among consumers towards donation and reward-based crowdfunding. This research suggests that crowdfunding websites should be redesigned to prevent online fraud and corruption in order to encourage consumer engagement.